ANALISIS PROSES PROMOSI JABATAN APARATUR SIPIL NEGARA Studi Kasus: Proses Promosi Jabatan Stuktural Eselon II di Pemerintah Daerah Daerah Istimewa Yogyakarta Tahun 2014 - Atmojo, Muhammad Eko (ARISTO, 2016)
Government implementation system should support by apparatus resources with professional competence. Think to create the good governance system as well as clean and good then need the resources of the competent apparatus. To creating the resources of the competent apparatus needs to reforming the bureaucracy in civil service sectoral. Government should give the special attention toward the civil service system in Indonesia. Especially in regeneration of structural functionary or functionary promote. The government of Yogyakarta Special Region had been used the different method to implementation the functionary promotion, such as used a few level with between administration selection, assessment center, and fit and proper test. The method had been used by the government of Yogyakarta Special Region with prospect it can be created the resources of the competent apparatus by professional, with the result that created the good governance and good public service.